The Relationship Between the Gut Microbiome-Immune System-Brain Axis and Major Depressive Disorder - Foster, Jane A.; Baker, Glen B.; Dursun, Serdar M. (Frontiers in Neurology, 2021)
Major depressive disorder (MDD) is a prominent cause of disability worldwide. Current antidepressant drugs produce full remission in only about one-third of MDD patients and there are no biomarkers to guide physicians in selecting the best treatment for individuals. There is an urgency to learn more about the etiology of MDD and to identify new targets that will lead to improved therapy and hopefully aid in predicting and preventing MDD. There has been extensive interest in the roles of the immune system and the gut microbiome in MDD and in how these systems interact. Gut microbes can contribute to the nature of immune responses, and a chronic inflammatory state may lead to increased responsiveness to stress and to development of MDD. The gut microbiome-immune system-brain axis is bidirectional, is sensitive to stress and is important in development of stress-related disorders such as MDD. Communication between the gut and brain involves the enteric nervous system (ENS), the autonomic nervous system (ANS), neuroendocrine signaling systems and the immune system, and all of these can interact with the gut microbiota. Preclinical studies and preliminary clinical investigations have reported improved mood with administration of probiotics and prebiotics, but large, carefully controlled clinical trials are now necessary to evaluate their effectiveness in treating MDD. The roles that several gut microbe-derived molecules such as neurotransmitters, short chain fatty acids and tryptophan play in MDD are reviewed briefly. Challenges and potential future directions associated with studying this important axis as it relates to MDD are discussed.